RELATIVE COMPETITIVENESS BETWEEN MAIZE HYBRIDS AND WILD POINSETTIA - Galon, Leandro (2021)
Maize is one of the main cereals cultivated worldwide and wild poinsettia is among the weeds that cause damage in grain production. The objective of this study was to evaluate the relative competitive ability of maize hybrids in the presence of a wild poinsettia biotype through experiments in replacement series. In preliminary experiments, it was determined the plant population in which the dry mass becomes constant. For the maize hybrids ‘Agroeste’, ‘Morgan’, ‘Nidera’, and ‘Velox’, as well as the wild poinsettia, the population was 20 individuals vase-1. Subsequently, experiments were carried out in replacement series in different combinations of species that varied the relative proportions (100:0, 75:25, 50:50, 25:75, and 0:100%). The analysis of the species' competitiveness was carried out using diagrams applied to the replacement experiments and by the relative competitiveness indexes. The height (PH), chlorophyll index (CI), leaf area (LA), and the shoot dry mass (DM) of the plants were evaluated 50 days after emergence. There was competition between the maize hybrids and the wild poinsettia; both were negatively affected, regardless of the proportion of plants, causing reductions in the species' PH, CI, LA, and DM. The competition between maize and wild poinsettia occurs for the same resources in the environment, and interspecific competition caused greater damage to maize and wild poinsettia than intraspecific competition. In general, it was observed that only the hybrids ‘Nidera’ and ‘Velox’ were more competitive than the wild poinsettia.